The science and art of testing in ice hockey: a systematic review of twenty years of research - Bournival, Michael; Martini, Gaëtan; Trudeau, François; Lemoyne, Jean (Frontiers in Sports and Active Living, 2023)
Introduction Ice hockey is a complex sport requiring multiple athletic and technical attributes. Considering the variety of tests developed, on-ice testing protocols have been created to measure the physiological and mechanical attributes associated with performance. To our knowledge, a lack of technical resources exists to help stakeholders opt for on-ice protocols from among those developed. It becomes crucial for researchers and practitioners to select relevant and context-specific procedures. This systematic review of the literature outlines an inventory of the on-ice tests that have been used in the domain of ice hockey research over the last twenty years, and summarize protocols mostly used in major athletic components. Methods A search was performed on three databases (PubMed, SPORTDiscus and Scopus) by following the PRISMA guidelines. Specific keywords were selected to find publications using on-ice testing protocols in the methodology. Four aspects of athletic attributes were used to categorize the protocols: aerobic capacity, acceleration-speed, agility-change of direction and ability to repeat skating sprints. Analyses were conducted regarding four categories of observations: population under study, on-ice reported test(s), outcomes measures and main findings. Results A total of 107 articles were included, resulting in 55 on-ice tests related to the on-ice assessments of four major athletic components: aerobic capacity (n = 7), acceleration-speed (n = 6), agility and change of direction (n = 23) and repeated skating sprint ability (n = 19). Testing in male and older cohorts (≥16 years old) predominates, with a primary focus on the competitive amateur level. The selected tests were mainly designed for assessing on-ice physiological responses and fitness (n = 38), talent identification-team selection (n = 19), efficiency of interventions (n = 17) and validation purposes (n = 16). Conclusion A prevalence of on-ice skating tests to assess the ability to repeat intense efforts, agility, acceleration and speed components exists, which are relevant and linked to match requirement. The wealth of on-ice tests used in the literature reflects the need to adapt the on-ice evaluation process to the population, constraints, and goals. This review is a valid toolbox and can benefit for researchers and practitioners interested in testing hockey players from different levels, with a variety of aims and needs, by helping them to select the relevant procedures to their environment and practice context.